The visuotectal projection following translocation of grafts within an optic tectum in the goldfish. - Gaze, R M (1983)
Rectangular grafts were translocated between the rostral and caudal tectum in adult goldfish. In some animals the optic nerve was also cut. After periods ranging from 161 to 378 days the retinotectal projections were mapped. The results showed that translocation of tectal grafts is followed by translocation of the corresponding part of the visuotectal map. In many cases the visual field positions projecting to points in the region between the grafts were abnormal and in some cases intercalated field positions were found across the borders between grafted and normal tissue. The results are taken as strong evidence for the existence of affinity labels on the tectum and their importance in the restoration of the retinotectal projection.